Diversidade de cupins e suas relações edáficas em savana estépica na formação Surumu, Roraima - Oliveira, Meiriane Nunes de (2018)
Termite fauna plays an important role in ecosystem engineering, acting on nutrient cycling, genesis of soils and maintenance of heterogeneity in savannas. This research aims at the analysis of the diversity and the action of termites on the edaphic attributes of the Surumu Formation, savanna environment in the state of Roraima. The termite diversity was estimated through a fast collection protocol plotted in Argisols and Planosols. Six species belonging to the families Rhinotermitidae (a single species) and Termitidae subdivided into the subfamilies Apicotermitinae (seven species), Nasutitermitinae (five species) and Termitinae (three species) were found. The faunistic composition of frequent species is similar in both soil classes, four species were considered eudominant, two dominant and three subdominants, but the composition of the six rare species differs in the soil classes. The epigeal species Amitermes excellens, the constructor of large termite mounds, is considered eudominant in the landscape. The results of the species richness, abundance and dominance of the Termitidae family in the Surumu Formation, resemble the cerrado and caatinga biomes. The nesting of termites presents six species that construct diffuse nests, six hypogeous species and only three species that construct epigeal nests. The dominant trophic group are the humivores, followed by the xylophagous, intermediates and reapers, being evident the correlation between nesting and feeding. Three species were designated exclusive of open environments, among them Cortaritermes intermedius and Grigiotermes sp. A did not show record of occurrence in the Amazon, evidencing still not detailed aspects about termite fauna in the study area, impelling questions for future research. The termite fauna plays a significant role in determining the differences between the material of termites of A. excellens and adjacent soils in the two soil classes, the concentration of clay by selection of fine particles of subsurface soils has been proven and explains the nutrient retention (N, P, K, Ca2+, Mg2+) and organic matter concentrated in the nests by the action of termites. There were significant differences in the density and volume of termite mounds in the two classes of soils studied, in the Argisols the density is low (13.5 termites per hectare) and the nests are higher (2.08 m) and bulky (25.48 m3ha-1e), already Plintosols density is high (40 termites per hectare) and nests are lower (1.57 m) and less voluminous (14.31 m3ha-1), this dynamics is caused by paleoclimatic, hydropedological conditions, clay availability, time and intra-specific competition. The calculated estimate of erosion and decay of termite mounds after colony death can create a mantle of up to 11.46 cm in Argisols and 18.89 cm in Plintosols, totaling 30.35 cm of material that will be returned to the soil system, enriching it with high concentrations of nutrient enriched clay. The bioturbation promoted by the species A. excellens modifies the landscape and creates islands of fertility, allowing association with the vegetation, maintaining the heterogeneity of the environment. The ability to modify the chemical and physical edaphic attributes evidences the importance of the ecosystem engineering of this species in the nutrient cycle and soil genesis in the Estoravian savannah of Roraima.